2001
DOI: 10.1185/0300799019117018
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Troxerutin and Carbazochrome Combination in the Treatment of Post-hemorrhoidectomy Status: A Randomized, Double-blind, Placebo-controlled, Phase IV Study

Abstract: Flavonoids, such as troxerutin, have been shown to be safe and effective agents for the treatment of chronic venous insufficiency. The fixed combination between troxerutin 150 mg and carbazochrome 1.5 mg (Fleboside ampoules) was previously shown to have a good efficacy and safety profile in non-surgical patients with acute uncomplicated hemorrhoids. The purpose of this randomized, double-blind, placebo-controlled study was to investigate the efficacy and tolerability of the active combination in the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…CSS is one of the oldest drugs that has been used for various indications, such as in surgical settings, 7 , 8 , 10 , 19 , 20 gastrointestinal bleeding, 4 , 5 trauma, 6 pulmonary hemorrhage, 9 refractory chronic prostatitis 21 , hereditary hemorrhagic telangiectasia, 22 or dengue vascular permeability. 23 , 24 Accordingly, CSS has applications other than as a hemostatic agent.…”
Section: Discussionmentioning
confidence: 99%
“…CSS is one of the oldest drugs that has been used for various indications, such as in surgical settings, 7 , 8 , 10 , 19 , 20 gastrointestinal bleeding, 4 , 5 trauma, 6 pulmonary hemorrhage, 9 refractory chronic prostatitis 21 , hereditary hemorrhagic telangiectasia, 22 or dengue vascular permeability. 23 , 24 Accordingly, CSS has applications other than as a hemostatic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Another important nucleus in medicinal chemistry is the N-acylhydrazone. The N-acylhydrazone scaffold (-CO-NH-N=CH-) is illustrated by the fusion between two subunits, imine and amide, which displays a broad spectrum of pharmacological activities, including antibacterial, antihemorrhagic, antitumor, and antidiarrhea properties [ 15 , 16 , 17 ]. The N-acylhydrazone derivatives are both proton donor and acceptor species, which are a required component of potent kinase inhibitors [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that TRX has multiple biological functions, such as antioxidative, anti-inflammatory and antiplatelet activities [13]. Pretreatment with TRX can induce cardioprotection by modulating the inflammatory response after myocardial ischaemia/reperfusion injury in rat models [4]. Pre-treatment with TRX can induce cardioprotection through modulating the inflammatory response after myocardial ischaemia/reperfusion injury in rat models [1].…”
Section: Introductionmentioning
confidence: 99%